2017
DOI: 10.1111/prd.12151
|View full text |Cite
|
Sign up to set email alerts
|

Dental calculus: the calcified biofilm and its role in disease development

Abstract: Dental calculus represents the first fossilized record of bacterial communities as a testimony of evolutionary biology. The development of dental calculus is a dynamic process that starts with a nonmineralized biofilm which eventually calcifies. Nonmineralized dental biofilm entraps particles from the oral cavity, including large amounts of oral bacteria, human proteins, viruses and food remnants, and preserves their DNA. The process of mineralization involves metabolic activities of the bacterial colonies and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(86 citation statements)
references
References 47 publications
1
77
1
7
Order By: Relevance
“…This unexpected finding may have occurred because although almost 90% of the participants reported adequate toothbrushing frequency, nearly 40% of the adolescents had one or more tooth with dental calculus and, therefore poor effectiveness of oral hygiene. Therefore, our findings may be explained because optimal oral hygiene is also influenced by the use of adequate tools, appropriate toothbrushing technique, and motivation …”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This unexpected finding may have occurred because although almost 90% of the participants reported adequate toothbrushing frequency, nearly 40% of the adolescents had one or more tooth with dental calculus and, therefore poor effectiveness of oral hygiene. Therefore, our findings may be explained because optimal oral hygiene is also influenced by the use of adequate tools, appropriate toothbrushing technique, and motivation …”
Section: Discussionmentioning
confidence: 94%
“…Therefore, our findings may be explained because optimal oral hygiene is also influenced by the use of adequate tools, appropriate toothbrushing technique, and motivation. 33 In this study, oral hygiene was assessed through toothbrushing frequency and oral hygiene effectiveness. The latter was measured according to the number of teeth with dental calculus.…”
Section: Discussionmentioning
confidence: 99%
“…A national survey in America reported that a high level of physical activity prevented periodontitis. Indeed, physical activity was positively associated with antibodies in the orange and blue complex related to healthy periodontal states [40]. In addition, it has been reported that periodontal disease often occurs in elderly individuals with poor health activities and conditions [41].…”
Section: Discussionmentioning
confidence: 99%
“…Patient participants were initially screened for availability on one of three data collection dates and the eligibility criteria. Eligible patient participants were adults aged 18 and over with good general health and no history of professional cleaning within the past 6 months, which increased the likelihood of readily detectable calculus . Ineligible patient participants were those with uncontrolled systemic disorders and a history of professional cleaning within the past 6 months.…”
Section: Methodsmentioning
confidence: 99%